Pengaruh Market To Book Value, Liquidity, Leverage, Altman Z-Score, Firm Size, Dan Profitabilitas Terhadap Keputusan Hedging (Studi Kasus Perusahaan Dalam Daftar JII70 2018-2020) - Risa Listiana; Niken Savitri Primasari (Jurnal Akuntansi dan Keuangan, 2022)
This aims of this research is to analyze the effect of market to book value, liquidity, leverage, altman z-score, firm size, and profitability partially on hedging decisions. The type of thisresearch isquantitative. The population is all of companies on JII70 (Jakarta Islamic Index 70) 2018-2020. The purposive sampling technique to selected until 36 samples companies. This research use logictic regression method. The following result are obtained that market to book value, firm size, and profitabilitypartially has a positive significant effect on hedging decisions. Liquidity and altman z-score has negative significant effect on hedging decisions. Leverage has no effect on hedging decisions.